Method to convert Kinect's 3D depth data to a 2D map for indoor SLAM - Kamarulzaman, Kamarudin (Institute of Electrical and Electronics Engineers (IEEE), 2014)
Proceeding of The 9th International Colloquium on Signal Processing and its Applications 2013 (CSPA 2013) at Kuala Lumpur, Malaysia on 8 March 2013 through 10 March 2013